High-flow nasal cannula: Evaluation of the perceptions of various performance aspects among Chinese clinical staff and establishment of a multidimensional clinical evaluation system - Wen, Ruoxuan; Hu, Xingshuo; Wei, Tengchen; Wang, Kaifei; Duan, Zhimei; Zhao, Zhanqi; Xie, Lixin; Xie, Fei (Frontiers in Medicine, 2022)
Objective: In order to facilitate education for clinical users, performance aspects of the high-flow nasal cannula (HFNC) devices were evaluated in the present study. A multidimensional HFNC clinical evaluation system was established accordingly. Methods: Clinical staff from Chinese hospitals were invited to participate in an online questionnaire survey. Four aspects, namely, temperature stability, flow rate stability, oxygen concentration stability, and humidification capacity were evaluated and clinical evaluation system was established using Analytic Hierarchy Process. Four commonly used HFNC devices were evaluated via the new scoring system. Results: A total of 1,015 questionnaires was distributed for clinical staff around China and 285 were valid and finally evaluated (97 doctors, 116 nurses, 70 respiratory therapists (RTs), and 2 other clinical staff). Eighty-seven percent participants used HFNC ≥1/week. Seventy-nine percent RTs used HFNC daily, which significantly differed from the usage frequency among doctors and nurses (P = 0.002). No significant difference of usage frequency was found between doctors and nurses (54.64% vs. 56.9%). The relative importance of the four performance aspects of the HFNC devices differed according to profession but not proficiency levels or usage frequency. Nurses considered the accuracy of oxygen concentration as the most important performance aspect and differed from doctors and RTs (P < 0.001). Doctors and RTs showed a more balanced opinion regarding oxygen concentration accuracy, flow rate accuracy, and humidification capability. The HFNC devices evaluated in the present study showed different performances in different aspects. Conclusion: Education of the clinical users for HFNC may be tailored according to the profession. Selection of HFNC devices in clinical practice should be maded according to their strengths and drawbacks.